A Systematic Review of Traditional Chinese Medicine Treatment for Allergic Rhinitis - Zhao, Xiaoyu; Chen, Xi (Journal of Contemporary Medical Practice, 2025)
Allergic rhinitis is a non infectious chronic inflammatory disease of the nasal mucosa mediated by immunoglobulin E (IgE). It is a disease characterized by nasal itching, paroxysmal continuous sneezing, watery nasal mucus, and nasal congestion. It is a common and frequently occurring disease in clinical practice, often recurring. In recent years, the incidence rate of the disease is increasing year by year, which brings inconvenience to the life of patients. At present, there is no cure for this disease in clinical practice. But traditional Chinese medicine treatment can effectively control symptoms, improve the body’s resistance, reduce the recurrence rate after treatment, and improve the quality of life of patients.